Policy Brief: Women at the Center of Climate Resilience:. Gender-Responsive Weather and Climate Information Services (WCIS) for East Africa - Nchanji, Eileen Bogweh; Ouya, Frederick Ochieng; Lutomia, Cosmas Kweyu; Mvuyibwami, Patrick; Byandaga, Livingstone; Kagabo, Desire (2026)
Significant gender disparities in access to and use of Weather and Climate Information Services (WCIS) must be addressed to ensure inclusive climate risk management. Policies and programs should intentionally integrate the voices of women, youth, refugees, internally displaced persons (IDPs), and persons living with disabilities (PLWDs). Expanding co-design and co-production of WCIS across East Africa is essential to deliver timely, relevant, and actionable information. Evidence from Kenya, Rwanda, Tanzania, and Uganda demonstrates that WCIS delivers tangible results. Between 38–49% of farmers reported bean yield increases of 0.2–0.3 t/ha, while 31–45% experienced smaller gains of up to 0.1 t/ha. Additionally, 30–33% of farmers avoided seasonal losses of up to USD 30, and 33–71% avoided losses of up to USD 100, thanks to impact-based early warning systems. However, these benefits are not reaching ev eryone equally. Women, youth, persons with disabilities, refugees, and internally displaced persons face barriers in access, voice, and decision-making power. Men dominate formal WCIS channels, while women often rely on informal networks and are restricted from acting on information even when they receive it. These disparities are driven largely by restrictive socio-cultural norms that limit access to agro-weather technol ogies and exclude women and other vulnerable groups from household and community decision-making. As these groups are highly dependent on climate-sensitive agriculture, they face disproportionate livelihood risks from climate variability and extremes. This brief presents key messages and policy options to close gender gaps and promote inclusive WCIS and stron ger policy frameworks. Strengthening inclusive access to accurate and timely weather and climate information will improve risk management, enhance adaptive capacity, and support productivity gains in the agriculture sec tor. The evidence is clear: when climate information is co-produced with communities, localised, and designed with gender inclusion, adoption increases, losses decline, and resilience strengthens. This brief outline priority actions for governments and development partners to scale proven models, mobilize finance, institutionalize co-production, and close the digital and gender divide in climate services.